2022
DOI: 10.1002/adma.202202309
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Circularly Polarized Luminescence with Tunable Handedness and Intensity Enabled by Achiral Dichroic Dyes in Cholesteric Liquid Crystal Medium

Abstract: Cholesteric liquid crystals (CLCs) are chiral supramolecular systems that self‐assemble into a highly regular helical arrangement in a liquid crystal (LC) medium. Such an arrangement is highly beneficial for the chiral enlargement effect on circularly polarized luminescence (CPL) signals. Dichroic dyes with rod‐like molecular structures can exhibit fluorescence anisotropy along both the long and short molecular axes owing to their transition dipole moment (TDM) vectors. In this work, a pair of donor–accepter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 54 publications
(61 reference statements)
0
12
0
1
Order By: Relevance
“…Furthermore, they allow various emitters with different electrostatic states (neutral, positive, and negative) and different sizes (fluorescent molecules and nanoclusters) to incorporate into these chiral media for CPL generation. 26 Most importantly, these chiral solid films are robust and flexible, showing great potential for real CPL applications.…”
Section: Helically Arranged Nanofibers At the Microscale For Cpl Gene...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they allow various emitters with different electrostatic states (neutral, positive, and negative) and different sizes (fluorescent molecules and nanoclusters) to incorporate into these chiral media for CPL generation. 26 Most importantly, these chiral solid films are robust and flexible, showing great potential for real CPL applications.…”
Section: Helically Arranged Nanofibers At the Microscale For Cpl Gene...mentioning
confidence: 99%
“…23,24 The arrangement of fibers is another factor that contributes to the properties of CPL and the development of new types of chiral materials for practical applications. [25][26][27] The introduction of fibrous morphologies boosts chiral science, acting as a chiral medium to create chiroptical active materials, endowing achiral luminophores with CPL properties from 0 (no chiroptical activity of achiral luminophores at the molecular level) to N (CPL emergence, amplification, and regulation at the fibrous aggregates) (Fig. 1).…”
Section: Linfeng Chenmentioning
confidence: 99%
“…While the quest for high-quality hard materials persists, there has been a surge in interest toward developing multifunctional soft materials. Soft materials may not possess the same level of strength and durability as hard materials, but their dynamic properties offer unique opportunities for the production of versatile advanced devices. Especially, smart soft materials have been designated as the cornerstone of the next generation of advanced devices and digital enhancement technologies. , Liquid crystals (LCs) with their controllable stimulus response and adaptive properties have been widely utilized in optoelectronic devices as one of the most promising soft materials. With the rapid advancement of chiral supramolecular chemistry in the past few decades, an increasing number of studies have focused on excellent circularly polarized luminescence (CPL)-active materials stemming from the regulation of a cholesteric LC (N*-LCs) medium through the rational design of chiral supramolecular self-assembly or co-assembly. , Normally, this kind of chiral self-assembled or co-assembled process can endow outstanding assembly function and give rise to the ordered and regular helical arrangement textures in N*-LCs, which is greatly beneficial to chiral amplification effect and chiral induction ability. More and more reports have demonstrated that N*-LCs can self-assemble as regular helical superstructure textures between chiral inducers and achiral dyes, which can effectively promote the chirality amplification effect of the achiral dyes through the chiral co-assembled process in the LC medium. Therefore, it is of great significance for the rational design of excellent supramolecular self-assembled and co-assembled CPL-active material.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Using the same CLCs, we also found that the dynamic CPL with tunable handedness and intensity could be successfully achieved by only changing the mass ratio of achiral dichroic dyes. [7] Our previous works revealed that the chiral transfer and induction efficiency could be increased not only by the chiral inducers [5a,8] but also by the achiral dichroic dyes. [9] Although extensive research efforts have been devoted to chiral co-assembled CPL materials by choosing various chiral inducers, [2b,10] very few works were concerned with achiral dichroic dyes in CLC.…”
Section: Introductionmentioning
confidence: 99%